Development and implementation of a clinical information system–based protocol to improve nurse satisfaction of end-of-life care in a single intensive care unit. Issue 3 (May 2022) - Pachchigar, R.; Blackwell, N.; Webb, L.; Francis, K.; Pahor, K.; Thompson, A.; Cornmell, G.; Anstey, C.; Ziegenfuss, M.; Shekar, K.
Abstract: Background: Patients treated in Australian intensive care units (ICUs) have an overall mortality rate of 5.05%. This is due to the critical nature of their disease, the increasing proportion of patients with multiple comorbidities, and advanced age. This has made treating patients during the end of life an integral part of intensive care practice and requires a high quality of care. With the increased use of electronic clinical information systems, a standardised protocol encompassing end-of-life care may provide an efficient method for documentation, communication, and timely delivery of comfort care. Objective: The aim of the study was to determine if an electronic clinical information system–based end-of-life care protocol improved nurses' satisfaction with the practice of end-of-life care for patients in the ICU. Design: This is a prospective single-centre observational study. Setting: The study was carried out at a 20-bed cardiothoracic and general ICU between 2015 and 2017. Participants: The study participants were ICU nurses. Intervention: Electronic clinical information–based end-of-life care protocol was used in the study. Outcome: The primary outcome was nurse satisfaction obtained by a survey. Results: The number of respondents for the before survey and after survey was 58 (29%) and 64 (32%), respectively. There was a significant difference between the before survey and the after survey with regard to feeling comfortable in transitioning from curative treatment (median = 2 [interquartile range IQR = 2, 3] vs 3 [IQR = 2, 3], p = 0.03), feeling involved in the decision to move from curative treatment to end-of-life care (median = 2 [IQR = 2, 2] vs 2 [IQR 2, 3], p = 0.049), and feeling religious beliefs/rituals should be respected during the end-of-life process (median = 4 [IQR = 3, 4] vs. 4 [IQR = 4, 4], p = 0.02). There were some practices that had a low satisfaction rate on both the before survey and after survey. However, a high proportion of nurses were satisfied with many of the end-of-life care practices. Conclusion: The nurses were highly satisfied with many aspects of end-of-life care practices in this unit. The use of an electronic clinical information system–based protocol improved nurse satisfaction and perception of quality of end-of-life care practices for three survey questions.